Nesprin-2G, a Component of the Nuclear LINC Complex, Is Subject to Myosin-Dependent Tension - Arsenovic, Paul T; Ramachandran, Iswarya; Bathula, Kranthidhar; Zhu, Ruijun; Narang, Jiten D; Noll, Natalie A; Lemmon, Christopher A; Gundersen, Gregg G; Conway, Daniel E (Biophysical journal, 2016)
The nucleus of a cell has long been considered to be subject to mechanical force. Despite the observation that mechanical forces affect nuclear geometry and movement, how forces are applied onto the nucleus is not well understood. The nuclear LINC (linker of nucleoskeleton and cytoskeleton) complex has been hypothesized to be the critical structure that mediates the transfer of mechanical forces from the cytoskeleton onto the nucleus. Previously used techniques for studying nuclear forces have been unable to resolve forces across individual proteins, making it difficult to clearly establish if the LINC complex experiences mechanical load. To directly measure forces across the LINC complex, we generated a fluorescence resonance energy transfer-based tension biosensor for nesprin-2G, a key structural protein in the LINC complex, which physically links this complex to the actin cytoskeleton. Using this sensor we show that nesprin-2G is subject to mechanical tension in adherent fibroblasts, with highest levels of force on the apical and equatorial planes of the nucleus. We also show that the forces across nesprin-2G are dependent on actomyosin contractility and cell elongation. Additionally, nesprin-2G tension is reduced in fibroblasts from Hutchinson-Gilford progeria syndrome patients. This report provides the first, to our knowledge, direct evidence that nesprin-2G, and by extension the LINC complex, is subject to mechanical force. We also present evidence that nesprin-2G localization to the nuclear membrane is altered under high-force conditions. Because forces across the LINC complex are altered by a variety of different conditions, mechanical forces across the LINC complex, as well as the nucleus in general, may represent an important mechanism for mediating mechanotransduction.